Four new species of Hecabolus Curtis, 1834 (Braconidae, Doryctinae) from south and southwestern Brazil, with notes on the morphological variation and geographic distribution of H. mexicanus Zaldívar-Riverón & Belokobylskij, 2009 - Castañeda-Osorio, Rubén; Belokobylskij, Sergey A.; Zaldívar-Riverón, Alejandro (European Journal of Taxonomy, 2022)
Four new species of the braconid wasp genus Hecabolus Curtis, 1834 (Doryctinae Foerster, 1863) are described for the Neotropical region in south and southwestern Brazil: H. acutus sp. nov., H. chrisaxeli sp. nov., H. gavinbroadi sp. nov., and H. transversalis sp. nov. We also report the morphological variation of females and males of H. mexicanus Zaldívar-Riverón & Belokobylskij, 2009, originally described based on a single female, and provide its first precise geographical distribution records. An updated key to the 13 described species of Hecabolus is provided.